Media bias in economic news: A factor 20 - Matthias Heinz; Johan Swinnen (Katholieke Universiteit Leuven, LICOS Centre for Institutions and Economic Performance, 2013)
We reviewed all articles reporting on job creation and job destruction by companies in Germany between December 2000 and September 2008 in Die Welt, one of the leading German newspapers, using experiments to test our selection criteria. There is a large difference in coverage of job creation and job shedding. Despite the fact that the economic situation in Germany improved over the period (unemployment rate fell by 2.0%), more than ten times as many articles report on negative employment news compared to positive news. When we control for the number of jobs involved, we find an even stronger bias: on a per-job basis, the bias to downsizing increases to a factor greater than 20. Additional tests indicate that these effects are similar in other leading German newspapers.
Keywords: L82; D83; 330; Media economics; rational ignorance; negative news coverage; Zeitung; Personalabbau; Personalbeschaffung; Medienökonomik; Deutschland